2017
DOI: 10.1111/jsap.12635
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of metronomic cyclophosphamide chemotherapy in a UK population of cancer‐bearing dogs: a retrospective study

Abstract: Metronomic cyclophosphamide is generally well-tolerated in dogs but the incidence of sterile haemorrhagic cystitis in this study is higher than previously reported. Regular urinalysis is recommended for all dogs receiving cyclophosphamide chemotherapy, as early detection of haemorrhagic cystitis may prevent development of more serious disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…MC with cyclophosphamide was related to mild toxicity and SHC resolved with the use of supportive treatment. SHC was documented in a total of 31% of dogs in this study, which is similar to previous reports . However, this is likely biased by the study population and the shorter survival time.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…MC with cyclophosphamide was related to mild toxicity and SHC resolved with the use of supportive treatment. SHC was documented in a total of 31% of dogs in this study, which is similar to previous reports . However, this is likely biased by the study population and the shorter survival time.…”
Section: Discussionsupporting
confidence: 89%
“…Diuretics were not used concurrently in any of the dogs receiving MC though they might be considered to reduce the likelihood of SHC in treated dogs, as reported in a recent study . Furthermore, monitoring for haematuria was not standardized between the different institutions, which may lead to under‐reporting of SHC …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall incidence of SHC in the University of Wisconsin‐Madison dogs enrolled in this study was 8.9%. This is comparable to other studies, in which SHC was found in 3.8% to 9.0% of pulse‐treated dogs, and in 3.6% to 32% of metronomic CP‐treated dogs Metronomic CP was a significant risk factor for SHC in our study. Cumulative CP doses were nearly 3‐fold higher with metronomic compared to pulse protocols, and higher cumulative doses are a risk factor for SHC .…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] The presence of SHC was defined as newly observed haematuria with pollakiuria or stranguria and a negative urine culture, at any time during CP treatment. 18 BM and GI toxicities were determined from the history, physical examination and CBC during the 7 to 10 days after intermittent CP administration. Toxicities were graded from 0 to 5 based on VCOG-CTCAE v1.1 criteria.…”
Section: Introductionmentioning
confidence: 99%